Pemberdayaan PKK dalam Perawatan Jenazah : Studi Kasus Desa Punggul, Jawa Timur - Nandya Dwi Agusti; Cantika Dwi Maydina; M. Firdaus Kurniawan (Faculty of Social and Political Science, 2024)
Women's empowerment is an important focus for the world as stated in SDGs point 5 on gender equality which is key in achieving sustainable development and community welfare. PKK (Empowering Family Welfare) as a forum for empowering women or housewives is the main subject in research on training activities for caring for the dead. The targets of this research are PKK women in Punggul Village, Gedangan District, Sidoarjo Regency. The research method used is a qualitative method with a phenomenological approach to understand the experiences and perspectives of PKK Village Ibu Punggul, Ibu 'Modin', and the Community Service Team of Institut Teknologi Sepuluh Nopember in the case of handling corpses. Data collection in this study was through direct observation and field observation during the implementation of the simulation of caring for the corpse. Then, the research results are presented based on descriptive data analysis. The service activity of caring for the corpse began with a theoretical presentation led by the community service team and continued with a simulation led by the 'Modin' together with PKK women. Different views began to emerge at the opening of the discussion session, starting from the use of types of soap, toiletries, prayer leaders, and women's participation in caring for the corpse. This training has a positive impact, both in terms of preserving cultural values and strengthening social cohesion.